Usage of War History Monuments of Khmelnystkii Region in Teaching and Educational Process - Mykola Kabachynskyi (Pedagogical Discourse, 2013)
On the basis of theoretic-empirical research the posibility of usage of war history monuments of Khmelnystkyi region that is permanent fortification constructions of strengthened areas, in teaching and educational process has been analyzed in the article.